My Thirty-Three Year's Dream : the Autobiography of Miyazaki Toten. - Toten, Miyazaki (Princeton library of Asian translations., 2014)
Annotated by Professors Jansen and Eto, the book illuminates the experiences of Miyazaki's generation with Western culture and the development of an Asian consciousness. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly incr.